Analisis Hubungan Nilai Tukar Nelayan Dengan Jenis Tangkapan Nelayan Di Desa Pengambengan, Kecamatan Negara, Kabupaten Jembrana, Bali - Ida Bagus Ketut Ravidhya Krisna Sekar; I Gusti Ngurah Putra Dirgayusa; Ni Luh Putu Ria Puspitha (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
This research aims to determine the fishermen’s exchange rate (NTN) and how the catch composition could affect the income of purse sein fishermen in Pengambengan Village. The object of the research is purse sein fishermen in Pengambengan Village, sampling has carried out by using purposive technique, and data was collected using questionnaires and interviews. The method used in this research are the NTN calculation method and multiple linear regression statistical method with hypothesis test, T-tets, F-test, and the coefficient of determination (adjusted R2 Square). The results show in the harvest season, almost all of the fishermen experienced a surplus (NTN above 100), while in the famine season only fishermen with high profit-sharing system experienced a surplus and the other experienced a disadvantage. For both of the two seasons, the fishermen’s catch composition are consist of lemuru, tongkol and layang; base on the T-test results, lemuru catch affect significantly on fishermen’s income during the harvest season, and layang catch affect the income of fishermen in the famine season. somultaneously the catch composition, lemuru, tongkol and layang affect fishermen income compared only 1 type of fish catch, and seen from the Coefficient of Determination by 6,6 % in the harvest and by 7,5 % in the famine season. The fishermen’s income is also influenced by other variables which are not included. in the model.